Chronic impairment of neurovascular coupling and cognitive decline in young survivors of severe traumatic brain injury - Zsofia Dina Magyar-Sumegi; Mark Csendes; Dominika Lendvai-Emmert; Gabriella Sebestyen; Viktoria Tamas; Szabolcs Bandi; Andras Czigler; Andriy Yabluchanskiy; Stefano Tarantini; Zoltan Ungvari; Endre Czeiter; Krisztina Amrein; et al. (GeroScience, 2025)
Severe traumatic brain injury (TBI) leads to chronic cognitive decline, imposing a significant societal burden. The regulation of cerebral blood flow (CBF) is critical for cognitive function, and acute disruptions in CBF regulation predict poor TBI outcomes. However, the long-term effects of TBI on CBF regulation and their association with cognitive function remain poorly understood. This study aimed to investigate whether severe TBI results in chronic CBF dysregulation and whether this contributes to long-term cognitive deficits. Additionally, we examined the role of TBI-induced insulin-like growth factor 1 (IGF-1) deficiency in cerebrovascular dysfunction. We assessed cognitive function, basal CBF (via phase contrast MRI), CBF autoregulation (via transcranial Doppler), and neurovascular coupling (NVC) in 33 TBI survivors (mean age 37.6 years, ~ 10 years post-injury) and 21 age-matched healthy controls. Serum IGF-1 levels were also measured. TBI survivors exhibited significant impairments in memory and executive function compared to controls. While basal CBF and autoregulation remained intact, NVC responses were chronically impaired and correlated with cognitive deficits. However, IGF-1 levels did not differ between groups and were not associated with NVC impairment or cognitive function. Our findings indicate that severe TBI results in chronic impairment of neurovascular coupling, which likely contributes to long-term cognitive deficits. These results highlight the need for further research to identify underlying neurovascular mechanisms and develop interventions to restore NVC and cognitive function in TBI survivors.

Impact of repeated bouts of eccentric exercise on myogenic gene expression - Andreas Costa; Hicham Dalloul; Hargita Hegyesi; Peter Apor; Zsolt Csende; Levente Racz; Mark Vaczi; Jozsef Tihanyi (European Journal of Applied Physiology, 2007)